Memories of distant mountains : illustrated notebooks, 2009-2022 - Pamuk, Orhan, 1952- (Alfred A. Knopf, 2024)
"For fourteen years, Orhan Pamuk kept a record of his daily thoughts and observations, entering them in small notebooks and illustrating them with his own paintings. This book combines those notebooks into one volume. In words and pictures, he writes about his travels around the world, his family, his writing process, and his complex relationship with his home country of Turkey. He charts the seeds of his novels and the things that inspired his characters and the plots of his stories. Intertwined in his writings are the vibrant paintings of the landscapes that surround and inspire him. A beautiful object in its own right, in Memories of Distant Mountains, readers can explore Pamuk's intoxicating inner world and can have a fascinating, intimate encounter with the art, culture, and charged political currents that have shaped one of literature's most important voices"--